Chemoresistance of cancer floating cells is independent of their ability to form 3D structures: Implications for anticancer drug screening. Issue 4 (7th September 2018) - Kaushik, Vivek; Yakisich, Juan S.; Way, Lillian Frances; Azad, Neelam; Iyer, Anand K. V.
Abstract: Three‐dimensional (3D) culture systems such as floating spheroids (FSs) and floating tumorspheres (FTs) are widely used as tumor models of chemoresistance. FTs are considered to be enriched in cancer stem‐like cells (CS‐LCs). In this study, we used cancer cell lines (lung H460, prostate LnCAP, and breast MCF‐7) able to form FSs under anchorage‐independent conditions and compared with cell lines (prostate PC3 and breast MDA‐MB‐231) that cannot form FSs under similar conditions. Independent of their ability to form FTs all cell lines growing under anchorage‐independent conditions become highly resistant to obatoclax, colchicine, and hydroxyurea. We used anti‐E‐cadherin antibody (that blocked the formation of FSs) and demonstrated that floating LnCAP cells showed similar chemoresistance regardless of the formation of spheroids. Our results demonstrate that the development of chemoresistance is not because of the formation of a complex 3D structure and/or enrichment of CS‐LCs but is likely the result of cell detachment per se and their ability to survive under anchorage‐independent conditions. We propose that FSs and FTs could be useful models to study chemoresistance of cancer cells associated with cell detachment (e.g., circulating tumor cells) but they may not be representative of other types of chemoresistance that arise in vivo in attached cells. Abstract : In this study, we used five different cancer cell lines to demonstrate that floating cells become highly resistant to obatoclax, colchicine, and hydroxyurea independent of their ability to form floating spheroids (FSs). We used anti‐E‐cadherin antibody (that blocked the formation of FSs) and demonstrated that floating LnCAP cells showed similar chemoresistance regardless of the formation of spheroids. Our results demonstrate that the development of chemoresistance is likely the result of cell detachment per se and their ability to survive under anchorage‐independent conditions.